DEKONSTRUKSI STRUKTUR POLITIK PUSAT DAN PENGUATAN SUMBERDAYA MOBILISASI DI WILAYAH PINGGIRAN SEBAGAI BASIS MUNCULNYA GERAKAN PETANI DI LAMPUNG - Hartoyo, Hartoyo; Soetarto, Endriatmo; Dharmawan, Arya Hadi; Lawang, Robert M.Z (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2010)
Contemporary peasant movements are still important to be studied, especially under the reformation era (or the democracy transition). The objective of this study were to analyze the relationship of the determinant factors on peasant movement. Qualitative approach was applied in this case. Data was employed in triangulation using dept interviews, documentations, and secundary data. Result showed that the combination of political opportuniiq structure and structure of resource mobilization affords groups a certain structural potential for action, they remain, in the absence of two other factors, insuffisient to account for peasant movement. The two factor were the sub-culture of peasant opposition as the antecedent factor and collective framing as the mediating factor.